Edukasi Berbasis Audio Visual Guna Peningkatan Pengetahuan Tentang Penggunaan Obat Hipertensi di Desa Sukolilo - Devi Setya Putri; Alvi Ratna Yuliana; Nila Putri Purwandari; Luluk Cahyanti (Jurnal Pengabdian Bidang Kesehatan, 2023)
Hypertension is a disorder in the blood vessels that causes blood pressure to increase, causing the heart to pump harder to circulate blood to organs and tissues throughout the body. The incidence of hypertension in Indonesia continues to increase because the majority of people do not take medication and do not regularly take medication because they feel healthy. Therefore, people with hypertension must receive treatment to reduce mortality and morbidity associated with hypertension. This requires knowledge regarding the use of hypertension medication by providing education using audio-visual media